The cost of housing for low-income renters - Robert Joyce; Matthew Mitchell; Agnes Norris Keiller (Institute for Fiscal Studies (IFS), 2017)
The "affordability" of housing is one of the most prominent domestic public policy issues of the day, and for good reason. The housing that people are in is an important determinant of their well-being, and it is something on which people - especially those on lower incomes - typically spend a substantial fraction of their income. Changes in the price of obtaining a given standard of housing can therefore significantly affect living standards. This report documents changes in housing tenure and analyses changes in the cost of renting.
Keywords: 330